Pendapat Madzhab Syafi’i Tentang Praktik Jual Beli Rambut - Ulfah Latifah; Santi Rahmawati (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2022)
Buying and selling is an activity carried out by everyone to meet various needs, both in the form of physical needs and spiritual needs. The aim of this research is to obtain data and information about the opinion of the Syafi'i Madhhab regarding the sale and purchase of hair, both natural human hair and synthetic hair. The research method is descriptive research with normative and sociological legal approaches. The results of the study show that buying and selling hair according to the Madzhab including the Shafi'i Madhhab is not allowed according to Islamic law itself, buying and selling real hair is forbidden because hair is a member of the human body that cannot be traded while synthetic hair has differences of opinion looking at the purpose of using hair extensions, factors that cause buying and selling hair due to economic factors, the number of enthusiasts of hair extensions and following current trends as well as a lot of natural human hair needed for hair extensions.